Numerical investigation of indoor air quality in a chemical laboratory subjected to gaseous cotaminants - Ayman Ahmed Mohamed Farid Shaaban; Essam E.Khalil Hassan Khalil; Mahmoud Ahmed Fouad; Samy Morad Morcos (Cairo : Ayman Ahmed Mohamed Farid Shaaban, 2013)
Indoor air quality inside chemical laboratories subjected to gaseous contaminants was investigated numerically throughout the current research using Ansys Fluent 13. The model was built and mesh was generated using Gambit 2.2.30 yielding around 1.4 million cells. Validation against experimental data from literature was done with absolute percentage error of 9.4%. five perameters that may affect indoor air quality inside the lab were investigated: Air Changes per Hour (ACH)
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Mechanical Power Engineering
Issued also as CD
Keywords: Chemical laboratories; Indoor air quality; Valilation